Tatag Teteg Tutug: Resilience with Local Values and Wisdom in Individuals with Disabilities with a Javanese Background - Munandar, Aris (PT. Anagata Sembagi Education, 2024)
People with disabilities experience many obstacles and problems that affect their personal and social acceptance. Despite facing challenges, not all individuals with disabilities are in a bad situation, but are able to get up and continue their lives. The condition of being able to get up and keep fighting is usually called resilience. Resilience is influenced by many factors, both from within the individual and the environment including the values and habits that exist in society. The purpose of this research is to find out how individuals experience disability and what its impact is, compare resilience theories and explore local values that influence. Research with a qualitative case study approach with informants of individuals with non-congenital disabilities totaling 7 people with male and female gender with Javanese ethnic background and domiciled in the Yogyakarta and Central Java regions. Data collection methods through interviews, observations, documents and audio. The data analysis used is data reduction, data presentation and conclusion drawing. The results of this study are that all informants were previously non-disabled and experienced accidents so that they experienced disabilities that had a direct impact on physical and psychological. There are differences between resilience theories from outside, outside the Javanese tribe with the findings in the research conducted such as characteristics, protective factors and risk factors. There are several findings of local values and wisdom such as the concept of tatag teteg tutug as a model of resilience in Javanese tribes. Then the value of local wisdom nrimo ing pandum, sadranan and ruwahan are carried out so that they contribute to strengthening the resilience of individuals with disabilities